Bibliographic Coupling Analysis IR4.0: Challenges and Opportunities in Southeast Asia - Mohamad Reeduan, Mustapha; Muhammad Ashraf, Fauzi; Puteri Fadzline, Muhamad Tamyez; So, Idris Gautama; Gui, Anderes (JES, 2024)
The fourth industrial revolution, known as Industry 4.0 or IR4.0, has garnered global attention for its transformative potential in revolutionizing manufacturing and industrial processes. This research conducts a bibliometric analysis using data from the Scopus database and the VOSviewer application to explore the current research landscape of IR4.0 in Southeast Asia. Findings reveal seven thematic clusters representing various aspects of IR4.0 integration and performance in the region. These clusters highlight the challenges, opportunities, and emerging themes surrounding IR4.0 adoption and implementation. Additionally, the study underscores the significance of Southeast Asian countries, particularly developing nations, in driving economic development through IR4.0 technologies. Insights from this study can inform business owners, policymakers, and academia about the evolving landscape of IR4.0 in Southeast Asia, aiding in strategic decision-making and technology adoption. Furthermore, the study suggests that the future of IR4.0 in the region hinges on the development of effective strategies, models, and technologies to enhance its implementation and impact.